Accomplishments from a decade of SCADA implementation in Idaho's Payette Valley - Sauer, Brian W., author; Shurtleff, Ronald, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2010)
Irrigated agriculture began in southwest Idaho's Lower Payette Valley in the 1880's. By 1900, over 30,000 irrigated acres had been developed, served by a system of over 20 canals diverting natural flows. High springtime river flows were often reduced to a trickle by August. Two Bureau of Reclamation dams were built to provide supplemental storage and to bring another 53,000 acres into production. Like many early canal systems, the Payette Valley canals were built with only a few manually operated water control structures or water measurement devices. Diversions were difficult to control due to variable river flows and much water was wasted. Water rights were difficult to administer, due to the lack of accurate water measurement. In dry years there were often disputes among users on different canals as natural flows declined. In 1997, the first canal headworks in the Payette were automated, utilizing solar power and simple off-the-shelf components. The success of this single project encouraged more irrigation entities to improve water control capabilities utilizing SCADA. New control structures were built and automated and communication links were put in place to monitor canal operations and to update water accounting. Today, there are over 40 automated control gates, 14 telemetered water measurement sites, and 11 new water measurement structures. Diversion data daily and accurately account for water use in the basin. Telemetry has enabled canal operators to monitor facilities and to respond quickly to changing water needs or emergency situations. Canal systems in the valley are being operated more efficiently, reducing both diversion rates and operational spills. This more efficient operation has helped to improve water supply reliability. These changes have also served to bring a greater sense of cooperation to water users throughout the Payette Valley.
Meeting irrigation demands in a water-challenged environment
A decade of SCADA implementation
Presented at Meeting irrigation demands in a water-challenged environment: SCADA and technology: tools to improve production: a USCID water management conference held on September 28 - October 1, 2010 in Fort Collins, Colorado.